Design of a novel THz sensor for structural health monitoring applications - Pavia, J. P. (2021)
In this paper, we propose a study on the characterization, design and simulation of a THz sensor for applications in Structural Health Monitoring (SHM). The proposed sensor is assembled using two frequency selective surfaces (FSSs) based on metamaterial wire resonators. We present a theoretical model to describe its electromagnetics which is used not only to understand the physical principles underlying the functioning of the sensor but also to determine a set of optimized parameters for its operation in the THz window from 395 GHz to 455 GHz. We present our numerical simulations, involving both electromagnetic and mechanical simulation techniques, to determine the reflectance profile of the sensor as a function of applied force. In this study we considered the possibility of using two thermoplastic polymers as host materials: High-Density PolyEthylene (HDPE) and PolyTetraFluoroEthylene (PTFE). The two sensors have a good dynamic range and comparable characteristics. However, we found that with HDPE it is possible to construct a sensor with a more linear response, although not as sensitive as in the case of PTFE. With HDPE we are able to pass from a situation of full transparency to almost full opacity using only its linear operating zone.